Improving Students’ Vocabulary Mastery using Interactive Multimedia - Refika Andriani (Universitas Lancang Kuning, 2016)
The purpose of the research is to find out wheter Interactive Video Multimedia can better improve thestudents’ vocabulary mastery at the grade II A students of Madrasah Ibtidaiyah Negeri 2 Pekanbaru, and to find out factors that influence it. In collecting the data, the researcher used vocabulary test, observation checklist, filed notes, and interview. This classroom action reasearch consisted of three cycles and three meetings of each cycle.Based on the findings, the use of interactive Video Multimedia could better improve students’ ability in vocabulary mastery at the Grade II A students of Madrasah Ibtidaiyah Negeri 2 Pekanbaru. The improvement was shown by the increasing of the students’ ability in vocabulary mastery. Finally, the classroom action research by using Interactive Video Multimedia could improve the vocabulary mastery by Grade II A students of Madrasah Ibtidaiyah Negeri 2 Pekanbaru.